Relationship between Blood Lipids, Lipoproteins and Ischemic Stroke - Karim Khan, Md Rezaul; Anwarullah, AKM; Saleheen, Md Shafiqus; Alam, SK Mahbub; Islam, Md Rafiqul; Alam, Syeda Tabassum (Bangladesh Journal of Neuroscience, 2014)
Objective: To find out the relationship of different lipids, lipoproteins and ischemic stroke patients in Bangladesh. Methodology: This case control study was conducted among the patients having ischemic stroke who were admitted in Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period from July, 1997 to June, 1999 and age, sex matched apparently healthy volunteers. Sixty ischemic stroke patients confirmed by CT scan of brain and sixty age and sex matched apparently healthy volunteers were enrolled as controls. 12 hours fasting lipid profile (Total cholesterol, LDL-cholesterol, HDLcholesterol and Triglyceride) was done for both ischemic stroke patients and healthy volunteers for comparison. The students (unpaired) t test was used to compare group means for lipids and lipoproteins. Chi square test, odds ratio with confidence interval were done to evaluate differences between the groups for other variables. P<0.05 was considered as minimum level of significance. Result: The mean age (±SD) of the patients and controls were 58.45±10.12 and 59.40±10.41 years respectively and 44 (73.3%) were male and 16 (26.7%) were female and male- female ratio was 2.75:1 in both cases and controls. Total cholesterol (Means) was 201.62±5.52 mg/dl and 169.13±3.49 mg/dl in cases and controls respectively (P<0.001). HDL cholesterol (Means) was 38.36±0.81 mg/dl and 44.03±0.84 mg/dl in cases and controls respectively (P<0.001). LDL cholesterol (Mean±SE) in ischemic stroke patients and controls were 125.45±4.63 mg/dl and 96.40±3.23 mg/dl respectively (P<0.001). Triglyceride (Mean±SE) in cases and controls were 188.50±9.35 mg/dl and 142.85±4.72 mg/dl respectively (P<0.001). Conclusion: This case-control study showed significant differences of serum lipids and lipoproteins (Total cholesterol, HDL cholesterol, LDL cholesterol and triglyceride) in ischemic stroke patients than the controls in our community. Bangladesh Journal of Neuroscience 2014; Vol. 30 (2): 96-103